﻿Therapeutic approach of glutathione/glutathione peroxidase-4 axis modulation in the light of ferroptosis - Tsvetelin Georgiev; Petya Hadzhibozheva; Yanka Karamalakova; Ekaterina Georgieva; Favas Perinkadakatt; Zlatomir Ilinov; Krasimir Petkov; Julian Ananiev (Pensoft Publishers, 2022)
In the 21st century beginning, the evidence of a new type of programmed cell death, different from apoptosis, began to accumulate. In 2012, the ferroptosis concept was officially introduced. It refers to a kind of cell death that is associated with iron accumulation in the cell, impaired redox potential, and ROS increment with concomitant lipid peroxidation. Ferroptosis plays an important role in the pathophysiology of several organ damages such as tumors, neurodegenerative, ischemia-reperfusion, inflammatory diseases, and others. In ferroptosis, the leading mechanism is the glutathione (GSH) depletion and inactivation of Glutathione peroxidase-4 (GPX4), which strongly shifts the oxidative balance in the cell, leading to the activation of certain signalling pathways to induce oxidative death. The article aims to focus attention on the modulation of the GSH/GPX axis as a key factor in the treatment of these diseases.